Single-cell RNA-sequencing analysis of aortic valve interstitial cells demonstrates the regulation of integrin signaling by nitric oxide - Majumdar, Uddalak; Choudhury, Talita Z.; Manivannan, Sathiyanarayanan; Ueyama, Yukie; Basu, Madhumita; Garg, Vidu (Frontiers in Cardiovascular Medicine, 2022)
Calcific aortic valve disease (CAVD) is an increasingly prevalent condition among the elderly population that is associated with significant morbidity and mortality. Insufficient understanding of the underlying disease mechanisms has hindered the development of pharmacologic therapies for CAVD. Recently, we described nitric oxide (NO) mediated S-nitrosylation as a novel mechanism for preventing the calcific process. We demonstrated that NO donor or an S-nitrosylating agent, S-nitrosoglutathione (GSNO), inhibits spontaneous calcification in porcine aortic valve interstitial cells (pAVICs) and this was supported by single-cell RNA sequencing (scRNAseq) that demonstrated NO donor and GSNO inhibited myofibroblast activation of pAVICs. Here, we investigated novel signaling pathways that are critical for the calcification of pAVICs that are altered by NO and GSNO by performing an in-depth analysis of the scRNA-seq dataset. Transcriptomic analysis revealed 1247 differentially expressed genes in pAVICs after NO donor or GSNO treatment compared to untreated cells. Pathway-based analysis of the differentially expressed genes revealed overrepresentation of the integrin signaling pathway, along with the Rho GTPase, Wnt, TGF-β, and p53 signaling pathways. We demonstrate that ITGA8 and VCL, two of the identified genes from integrin signaling pathway, which are known to regulate cell-ECM communication and focal adhesion, were upregulated in both in vitro and in vivo calcific conditions. Reduced expression of these genes after treatment with NO donor suggests that NO inhibits calcification by targeting myofibroblast adhesion and ECM remodeling. In addition, withdrawal of NO donor after 3 days of exposure revealed that NO-mediated transcriptional and translational regulation is a transient event and requires continuous NO exposure to inhibit calcification. Overall, our data suggest that NO and S-nitrosylation regulate the integrin signaling pathway to maintain healthy cell-ECM interaction and prevent CAVD.